Knowledge and Implementation of Clean and Healthy Living Behaviors (PHBS) Among School-Aged Children - Ramadhani, Dea Aulia; Ispriantari, Aloysia; Murtadho, Maulana Arif (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Clean and healty living behavior (PHBS) is an important indicator of school-aged children’s health. Good knowledge is expected to influence the implementation of PHBS. This study aimed to examine the relationship between knowledge and PHBS behavior among school-aged children at Public Elementary School of Kemiri 2, Kepanjen District, Malang Regency . Methods: This study used a quantitative cross-sectional design. The s,ample consisted of 87 students in grades 3–6 selected using total sampling. Data were collected via questionnaires and analyzed using the Chi-Square test to determine the relationship between knowledge and implementation of PHBS. Results: Most students had good knowledge (79.3%), but the majority showed adequate implementation of PHBS (74.7%). The statistical analysis showed that there was a significant relationship between knowledge and implementation of PHBS (p = 0.000). Conclusions: Based on these findings, nurses, in collaboration with schools and families, should design interventions to improve implementation of PHBS, which needs to be supported through habit formation, role models from teachers and parents, and the provision of a supportive school environment.